Sei uns willkommen, Pflegeroboter - Patrick Fehling (IUBH Internationale Hochschule, 2020)
– With the successive implementation of assistance technologies in nursing, robotics will also be included. It can be assumed that robotics will be used as a supplement to nursing staff, but also as a substitute. This is currently a very controversial issue, but in the long run it will undoubtedly be welcomed by a majority of the actors in nursing. In addition to care provided by assistance technologies/robotics, a not insignificant motive for their current and future use is the growing need for safety on the part of both care-giving relatives and professional carers. The fact that the nursing profession will have to face another change in the nursing paradigm as a result of the use of these technologies and the abandonment of many original nursing activities is as trivial as it is manageable in joint discourse.
Keywords: 330; Pflegeroboter; Pflegemensch; Robotik; Assistenztechnologie; Substitution; Behandlungspflege; Pflegeprofession; Paradigmenwechsel